# Nonhomogeneous DEs

#### Hussam Al-Tayeb

I got this book from WILEY by Erwin Kreyszig. It tells how to solved homogenous cauchy equations. It also covers simple nonhomogenous equations.
But it doesn't cover when we have nonhomogenous Cauchy equations like this one.
x2y''-xy'+y=lnx
How do I go about solving that equation?

I substituted x=e ^t and obtained the homogeneous solution yh=c1*x+c2*x
but there is still the partial solution (yp).
Any idea?

Last edited:
Related Differential Equations News on Phys.org

#### rbzima

I got this book from WILEY by Erwin Kreyszig. It tells how to solved homogenous cauchy equations. It also covers simple nonhomogenous equations.
But it doesn't cover when we have nonhomogenous Cauchy equations like this one.
x2y''-xy'+y=lnx
How do I go about solving that equation?

I substituted x=e ^t and obtained the homogeneous solution yh=c1*x+c2*x
but there is still the partial solution (yp).
Any idea?
You could use a series solution to this one. Although it might take some time, it might also clarify why the solution is what you say it is.

#### HallsofIvy

Homework Helper
I got this book from WILEY by Erwin Kreyszig. It tells how to solved homogenous cauchy equations. It also covers simple nonhomogenous equations.
But it doesn't cover when we have nonhomogenous Cauchy equations like this one.
x2y''-xy'+y=lnx
How do I go about solving that equation?

I substituted x=e ^t and obtained the homogeneous solution yh=c1*x+c2*x
but there is still the partial solution (yp).
Any idea?
Well, no, you didn't get that as a homogeneous solutions because you obviously (unless you made a typo) don't have two independent solutions! If you make the substitution
x= e^t then you get the homogeneous equation d^2y/dt^2- 2dy/dt+ y= 0 which has characteristic equation r^2- 2r+ 1= (r-1)^2= 0 and so gives the single solution y= e^t. The OTHER independent solution is y= te^t. Those two solutions, converted to x, since t= ln(x) are y= x and y= x ln(x).

But why stop at the homogeneous equation. Since the right hand side of your equation is ln(x), replacing x by e^t there gives ln(e^t)= t. Your equation reduces completely to
d^2/dt^2- 2dy/dt+ y= t. Trying y= At+ b, y'= A, y"= 0 so you have -2A+ At+ B= t: A= 1 and -2A+ B= -2+ B= 1 gives B= 3. Your general solution to the converted equation is
y= C1e^t+ C2xe^t+ t+ 3 which, using t= ln x, goes back to y= C1x+ C2x ln(x)+ ln(x)+ 3.

#### Hussam Al-Tayeb

HallsofIvy, I understood the y1= e^t and y2=te^t

But you said "Your equation reduces completely to d^2/dt^2- 2dy/dt+ y= t"
shouldn't it reduce to:
e^2t y'' - e^t y' + y = t ?

Last edited:

### Physics Forums Values

We Value Quality
• Topics based on mainstream science
• Proper English grammar and spelling
We Value Civility
• Positive and compassionate attitudes
• Patience while debating
We Value Productivity
• Disciplined to remain on-topic
• Recognition of own weaknesses
• Solo and co-op problem solving